Activity profiles of elite wheelchair rugby players during competition - Rhodes, J. M.; Mason, B. S.; Perrat, B.; Smith, M. J.; Malone, L. A.; Goosey-Tolfrey, V. L. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To quantify the activity profiles of elite wheelchair rugby (WCR) players and establish classification-specific arbitrary speed zones. In addition, indicators of fatigue during full matches were explored. Methods: Seventy-five elite WCR players from 11 national teams were monitored using a radio-frequency-based, indoor tracking system across 2 international tournaments. Players who participated in complete quarters (n = 75) and full matches (n = 25) were included and grouped by their International Wheelchair Rugby Federation functional classification: groups I (0.5), II (1.0-1.5), III (2.0-2.5), and IV (3.0-3.5). Results: During a typical quarter, significant increases in total distance (m), relative distance (m/min), and mean speed (m/s) were associated with an increase in classification group (P < .001), with the exception of groups III and IV. However, group IV players achieved significantly higher peak speeds (3.82 ± 0.31 m/s) than groups I (2.99 ± 0.28 m/s), II (3.44 ± 0.26 m/s), and III (3.67 ± 0.32 m/s). Groups I and II differed significantly in match intensity during very-low/low-speed zones and the number of high-intensity activities in comparison with groups III and IV (P < .001). Full-match analysis revealed that activity profiles did not differ significantly between quarters. Conclusions: Notable differences in the volume of activity were displayed across the functional classification groups. However, the specific on-court requirements of defensive (I and II) and offensive (III and IV) match roles appeared to influence the intensity of match activities, and consequently training prescription should be structured accordingly.